Learning media for the transliteration of Latin letters into Bima script based on android applications - Arik Aranta; I Gede Pasek Suta Wijaya; Ario Yudo Husodo; Gibran Satya Nugraha; Ramaditia Dwiyansaputra; Fitri Bimantoro; I Putu Teguh Putrawan (Journal of Education and Learning (EduLearn), 2021)
Preservation of Indonesian culture is an important thing that must be considered. One of the efforts that have been made in preserving culture is technological development implementation. In cultural preservation, based on data obtained from 45 respondents from the Bima community in Indonesia, 34.9% of the community does not understand the Bima script. It means that only 65.1% of the community can understand Bima script. This condition will continue to grow if there is no effort made to preserve the Bima script. Because people should have a comprehensive knowledge of the Bima script to understand its usage in writing and reading activities, people tend to have less desire to learn the Bima script. Mataram University is trying to develop creative and innovative learning products to learn the Bima script learning model in an interactive application using a smartphone to translate Latin letters into the script. This development aims to facilitate the process of learning Bima characters for the community. The method that has been used is to apply a string replacement algorithm based on the Bima script rules in the reference book containing the ancient Bima script. According to the experiment result, the alpha test value from 31 respondents is 99.36%, and the Beta test value from 45 respondents Bima society is 91.50%. It can be concluded that this application is feasible as a learning medium.